First record of a gravid female and neonate of the Lusitanian cownose ray, Rhinoptera marginata, from the eastern Mediterranean Sea - Basusta, A.; Ozer, E. I.; Sulikowski, J. A.; Basusta, N. (Wiley, 2012)
[Abstract Not Available]
Keywords: Rhinobatos-Rhinobatos; Demersal Assemblages; Common Guitarfish; Growth; Skate; Gulf; Age